Urban Rehabilitation: Reinventing a Productive Landscape Istanbul, Golden Horn Case Study - Canbay Türkyılmaz, Çiğdem; Pellitero, Ana Moya; Eliziario, Josue Silva; TÜRKYILMAZ, EMRAH (My University, 2013)
The international workshop “Golden Horn Urban Rehabilitation, Reinventing a Productive Landscape” was hosted at Istanbul Kültür University (IKU), Turkey, during the dates of the 4th to 11th July 2011. It counted with the bilateral collaboration of Istanbul Kültür University (IKU), Yildiz Technical University (YTU), Instituto Superior Manuel Teixeira Gomes (ISMAT), in Portugal and Studiomeb. The case study was located in the estuary area of Golden Horn, in Istanbul, and it was centred in the neighbourhoods of Balat, Fener and Hasköy, which are in an advanced process of urban and architectonic degradation. The paper presents our educative research methodology inside the program GreenEngines, developed during three years of continuous collaboration, and shows the results of our international research cooperation in this specific case study. Our pedagogic research method uses the principles of landscape urbanism, landscape planning, and environmental planning. Our research aim, specifically for this workshop was to educate students on the professional responsibility to create new sustainable planning alternatives for urban rehabilitation in deteriorated urban areas, and specifically, in the case study of Golden Horn in Istanbul. Our research questions were centred in how to preserve and protect the multicultural and multifunctional character of Golden Horn, evaluating its built and socio-cultural heritage, together with how to regenerate the physical urban tissue, reinventing a new productive landscape. Our research statement considered that to achieve a sustainable urban rehabilitation, it was necessary that the planning proposals should adapt to the cultural landscape and the local environment, creating a multifunctional character with different actors involved in the same urban context.
Keywords: Sustainable planning; urban rehabilitation; productive landscapes; architectural heritage; cultural landscape